Learning Experience on Digestive System: Does it Underlie Students' Eating Habits? - Dewi Mulyani; Ogi Danika Pranata (Indonesian Journal of Science and Education, 2025)
This study aimed to explore how biology education, particularly the topic of the digestive system, can serve as a basis for students to regulate their eating habits. The approach used in this research is a mixed-method approach, combining both quantitative and qualitative methods. The participants in this study comprised 69 twelfth-grade high school students. Data were collected using a questionnaire that included tests on digestive system content and eating habits, along with an open-ended section that required students to explain the eating patterns they adopted in their lives after studying the digestive system. The data collected were analyzed using Concurrent Triangulation. Students' understanding of the digestive system content remains relatively low, with an overall score percentage of 37.54%. Nevertheless, learning about the digestive system has positively impacted on the eating habits of most students, who have begun adopting healthier eating patterns. On the other hand, a small minority of students still neglect and have low awareness of maintaining healthy eating habits, indicating that further efforts are needed to enhance awareness and healthy habits among students. Support from parents, teachers, and the surrounding environment is crucial to ensure a balanced and nutritious diet for adolescents.